2015
DOI: 10.6002/ect.2013.0158
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: This study sought to determine the prevalence of hepatocellular carcinoma and other premalignant lesions in children with hereditary tyrosinemia type 1 who had undergone an orthotopic liver transplant at the Shiraz Transplant Center, in Shiraz, Iran. Materials and Methods: Between September 2006, and June 2011, thirty-six patients with hereditary tyrosinemia type 1 received a liver transplant from a deceased (whole or split) or a living-related donor. Clinical records and pathologic specimens, befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…There was 86% tumor-free survival at a median of 6.6 years[ 47 ]. Contrastingly, report from Iran has shown that HCC was present in 5 (23%) of the 22 explants, the diagnosis was confirmed before LT in 2 children[ 48 ].…”
Section: Pathogenic Risk Factorsmentioning
confidence: 95%
“…There was 86% tumor-free survival at a median of 6.6 years[ 47 ]. Contrastingly, report from Iran has shown that HCC was present in 5 (23%) of the 22 explants, the diagnosis was confirmed before LT in 2 children[ 48 ].…”
Section: Pathogenic Risk Factorsmentioning
confidence: 95%
“…Hypoglycemia secondary to hyperinsulinism and hypertrophic cardiomyopathy is a less frequent feature [ 9 , 10 ]. The condition, if not treated, progresses into life-threatening liver failure with an increased risk of hepatocellular carcinoma [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of HCCs in the pediatric age group has been reported in adolescents after 10 years of age, and occurrence of this tumor in young children is almost always associated with an underlying metabolic or viral liver disease (7,8). There have not been any studies regarding HCC in the pediatric age group from Iran.…”
Section: Discussionmentioning
confidence: 96%
“…The most common underlying cause in our center has been tyrosinemia. Tyrosinemia is an important cause of pediatric HCC, especially in the untreated patients (8). However, we had 1 case of PFIC (Progressive familial intrahepatic cholestasis).…”
Section: Discussionmentioning
confidence: 99%